Dismantling the patriarchal culture and optimizing gender equality in marriage law - Wahyudani, Zulham; Astiti, Ni Nyoman Adi; Tarantang, Jefry (Jurnal Anifa: Studi Gender dan Anak, 2023)
This article aims to examine the patriarchal culture in the Marriage Law No.1 of 1974 and how gender relations and law strengthen gender equality in the context of marriage and family in Indonesia. This regulation is considered gender biased because of legal norms that are influenced by the patriarchal system. The Marriage Law states that a husband is obliged to protect his wife. Meanwhile, the wife is positioned as a companion and complement. This patriarchal concept has led women to stereotypes, subordination, marginalization, and domestic violence. The research method is a literature review to listen to women’s voices and examine articles (regulations) considered gender biased from a gender perspective, namely indicators of justice (access, control, participation, and benefits) and gender injustice (subordination, discrimination, stereotypes, double/multiple burdens, and marginalization). The research results show that the patriarchal culture is implied in Law no. 1 of 1974 (Article 7 Paragraph (1) implies Subordination, Article 3 paragraph (2) implies Discrimination, Article 4 paragraph (2) letters a, b, and c implies Discrimination, Article 31 paragraph (3) implies Subordination and Double/multiple burdens, Article 34 paragraph (1) implies marginalization and subordination, and Article 34 paragraph (2) implies subordinate and double/multiple burdens). Furthermore, Articles 2, 34, and 41 are considered to contain subordination (degrading women), which state that all men can automatically become heads of families who, in terms of work, are able to support their families. Meanwhile, the gender approach believes that the head of the family is a man or woman who has the power and ability to provide for their family. The conclusion is that reformulation of the Marriage Law is needed to increase the importance of a culture of gender equality in a long-lasting and happy marriage. Therefore, it is necessary to understand the new norms from a gender justice perspective to improve the lives of Indonesian people.